Inequality and Preference: Leveraging Digital ICT Applications for Knowledge-Intensive Agriculture - Ahmad Badari Burhan (Mediator: Jurnal Komunikasi, 2023)
Digital ICT plays a strategic role in transforming input-intensive to knowledge-intensive agriculture. Its use has close relations to the farmers’ characteristics. This study aims to analyze the farmers’ characteristics and the intensity of utilizing various digital ICT applications/platforms. The survey was conducted on 150 smartphone-using farmers from Boyolali District, Central Java Province, Indonesia, accompanied by interviews and online observations. This research identifies digital divides and inequalities in leveraging Android farming applications, Facebook groups of farmers, WAG of farmers’ groups, Internet/Google information resources and YouTube. The correlation test indicated a significant correlation between gender, age, education, farming land area, farm income, internet quota budget, the availability of PC/Laptop (besides smartphones), and participation in farmers’ group with the intensity of leveraging some digital ICT applications. These correlations are unique and reflect farmers’ receptions and preferences for using digital ICT applications. This novelty is crucial for the development of knowledge-intensive agriculture that emphasizes the strategic role of development communication to facilitate knowledge sharing, involvement, and capacity development among farmers. Without understanding farmers’ characteristics and vulnerabilities, digital divide and inequality among farmers will continue to be reproduced.